What’s Harder: Reading, Writing, Listening or Speaking?: Ecuadorian Students’ Perceptions of the Four Macro-Skills - Mohini Tattersall, Rachel (Ecos de la Academia, 2021)
This study sought to better understand the relationship between Ecuadorian university students’ high school English learning experiences and their emotions regarding the four macro-skills. This built on previous studies about affect in second language learning. The main study methods employed were surveys with short answer sections, analysing the trends using t-tests, graphic representation and means, as well as coding non-empirical responses. The study found a weak relationship between students’ high school experiences and their perceptions for speaking and writing, and a very weak relationship for listening and reading. Findings provide an important contribution to work on EFL in Latin American tertiary contexts, as well as adding to the discussion of affect in second language learning. The study presents a meditation upon the role of emotion in learning that would be valuable for all EFL and second language professional